EXPEDIENTE - v16n2 - Soares, Adriana Benevides; Mendes, Deise Maria Fernandes; Valentim, Renata Patrícia Forain de; Barros, Rita Maria Manso de (Estudos e Pesquisas em Psicologia, 2017)
EXPEDIENTE - v16n2